Analysis of the Impact of Implementation of Integrated Manufacturing Information Systems (MES) in Increasing Production Efficiency in the Electronics Industry - Mizhir, Arham Bashir (IHSA Institute, 2025)
This research examines the impact of Manufacturing Execution System (MES) implementation on production efficiency in the electronics industry. As the electronics sector faces increasing demands for faster production cycles, higher quality standards, and cost optimization, the role of MES in streamlining production processes becomes critical. This study investigates how MES contributes to improving real-time data visibility, optimizing scheduling, enhancing quality control, and reducing downtime, all of which lead to higher production efficiency. The research also identifies the challenges associated with MES adoption, including high implementation costs, resistance to change, integration complexities, and data security concerns, while offering strategies for mitigating these issues. Through qualitative and quantitative analysis, the study highlights significant improvements in operational performance and competitive advantage post-MES adoption. The findings underscore the importance of MES as a strategic tool in the digital transformation of the electronics industry. This research contributes to the understanding of MES's role in manufacturing, offering practical insights for companies seeking to optimize their production processes and achieve sustainable growth. Additionally, the study provides a foundation for future research on MES integration with emerging technologies such as Artificial Intelligence (AI) and the Internet of Things (IoT) in manufacturing environments.